Analisis Pengenaan Pajak Atas Natura pada Perhitungan PPh 21 Pegawai Berdasarkan PMK Nomor 66 Tahun 2023 (Studi Kasus pada PT. ABC) - Nur Fitri Yani; Regina Jansen Arsjah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study was conducted to analyze the PPh 21 calculation for PT ABC employees in accordance with PMK Number 66 of 2023 and its impact on the income received by employees. This research focuses on analyzing PPh 21 calculation data on company salaries based on principles consistent with agency theory and accountability theory. PT ABC operates in the packaging machinery distributor sector, providing in-kind facilities to its employees such as vehicles, employee meals, uniforms, and sports facilities. This study was a single case study using a descriptive qualitative approach based on case studies. Data was collected through observation, interviews, archival records, and documentation studies. The analysis results indicate that several components of PT ABC's employee PPh 21 calculation require deductions for PPh 21 on Fringe Benefit in accordance with the provisions of PMK Number 66 of 2023. The addition of these PPh 21 calculation components for employees will affect the net income received by PT ABC employees. Thus, this research provides recommendations to provide education or information to employees regarding the additional PPh 21 calculation components for the Benefits in Fringe Benefit.